Difference between revisions of "009A Sample Final 1, Problem 1"
Jump to navigation
Jump to search
(2 intermediate revisions by the same user not shown) | |||
Line 1: | Line 1: | ||
<span class="exam">In each part, compute the limit. If the limit is infinite, be sure to specify positive or negative infinity. | <span class="exam">In each part, compute the limit. If the limit is infinite, be sure to specify positive or negative infinity. | ||
− | + | <span class="exam">(a) <math style="vertical-align: -14px">\lim_{x\rightarrow -3} \frac{x^3-9x}{6+2x}</math> | |
− | + | <span class="exam">(b) <math style="vertical-align: -14px">\lim_{x\rightarrow 0^+} \frac{\sin (2x)}{x^2}</math> | |
− | + | <span class="exam">(c) <math style="vertical-align: -14px">\lim_{x\rightarrow -\infty} \frac{3x}{\sqrt{4x^2+x+5}}</math> | |
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
!Foundations: | !Foundations: | ||
|- | |- | ||
− | | | + | |'''L'Hôpital's Rule, Part 1''' |
|- | |- | ||
| | | | ||
− | :: | + | Let <math style="vertical-align: -12px">\lim_{x\rightarrow c}f(x)=0</math> and <math style="vertical-align: -12px">\lim_{x\rightarrow c}g(x)=0,</math> where <math style="vertical-align: -5px">f</math> and <math style="vertical-align: -5px">g</math> are differentiable functions |
|- | |- | ||
− | | | + | | on an open interval <math style="vertical-align: 0px">I</math> containing <math style="vertical-align: -5px">c,</math> and <math style="vertical-align: -5px">g'(x)\ne 0</math> on <math style="vertical-align: 0px">I</math> except possibly at <math style="vertical-align: 0px">c.</math> |
− | |||
− | |||
− | |||
− | |||
|- | |- | ||
− | | | + | | Then, <math style="vertical-align: -18px">\lim_{x\rightarrow c} \frac{f(x)}{g(x)}=\lim_{x\rightarrow c} \frac{f'(x)}{g'(x)}.</math> |
− | |||
|} | |} | ||
+ | |||
'''Solution:''' | '''Solution:''' | ||
Line 35: | Line 31: | ||
|- | |- | ||
| | | | ||
− | + | <math>\lim_{x\rightarrow -3} \frac{x^3-9x}{6+2x}\,=\,\lim_{x\rightarrow -3}\frac{x(x-3)(x+3)}{2(x+3)}.</math> | |
|- | |- | ||
− | |So, we can cancel <math style="vertical-align: -2px">x+3</math>& | + | |So, we can cancel <math style="vertical-align: -2px">x+3</math> in the numerator and denominator. Thus, we have |
|- | |- | ||
| | | | ||
− | + | <math>\lim_{x\rightarrow -3} \frac{x^3-9x}{6+2x}\,=\,\lim_{x\rightarrow -3}\frac{x(x-3)}{2}.</math> | |
|} | |} | ||
Line 46: | Line 42: | ||
!Step 2: | !Step 2: | ||
|- | |- | ||
− | |Now, we can just plug in <math style="vertical-align: -1px">x=-3</math>& | + | |Now, we can just plug in <math style="vertical-align: -1px">x=-3</math> to get |
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
+ | \displaystyle{\lim_{x\rightarrow -3} \frac{x^3-9x}{6+2x}} & = & \displaystyle{\frac{(-3)(-3-3)}{2}}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{18}{2}}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{9.} | ||
+ | \end{array}</math> | ||
|} | |} | ||
Line 60: | Line 62: | ||
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
\displaystyle{\lim_{x\rightarrow 0^+} \frac{\sin (2x)}{x^2}} & = & \displaystyle{\lim_{x\rightarrow 0^+}\frac{2\cos(2x)}{2x}}\\ | \displaystyle{\lim_{x\rightarrow 0^+} \frac{\sin (2x)}{x^2}} & = & \displaystyle{\lim_{x\rightarrow 0^+}\frac{2\cos(2x)}{2x}}\\ | ||
&&\\ | &&\\ | ||
Line 70: | Line 72: | ||
!Step 2: | !Step 2: | ||
|- | |- | ||
− | |This limit is& | + | |This limit is <math>\infty.</math> |
|} | |} | ||
Line 81: | Line 83: | ||
|- | |- | ||
| | | | ||
− | + | <math>\lim_{x\rightarrow -\infty} \frac{3x}{\sqrt{4x^2+x+5}}=\lim_{x\rightarrow -\infty} \frac{3x}{\sqrt{x^2(4+\frac{1}{x}+\frac{5}{x^2}})}.</math> | |
|- | |- | ||
− | |Since we are looking at the limit as <math style="vertical-align: 0px">x</math> goes to negative infinity, we have <math style="vertical-align: -2px">\sqrt{x^2}=-x.</math> | + | |Since we are looking at the limit as <math style="vertical-align: 0px">x</math> goes to negative infinity, we have <math style="vertical-align: -2px">\sqrt{x^2}=-x.</math> |
|- | |- | ||
|So, we have | |So, we have | ||
|- | |- | ||
| | | | ||
− | + | <math>\lim_{x\rightarrow -\infty} \frac{3x}{\sqrt{4x^2+x+5}}\,=\,\lim_{x\rightarrow -\infty} \frac{3x}{-x\sqrt{4+\frac{1}{x}+\frac{5}{x^2}}}.</math> | |
|} | |} | ||
Line 97: | Line 99: | ||
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
− | + | \displaystyle{\lim_{x\rightarrow -\infty} \frac{3x}{\sqrt{4x^2+x+5}}} & = & \displaystyle{\lim_{x\rightarrow -\infty} \frac{-3}{\sqrt{4+\frac{1}{x}+\frac{5}{x^2}}}}\\ | |
− | + | &&\\ | |
− | + | & = & \displaystyle{-\frac{3}{\sqrt{4}}}\\ | |
− | + | &&\\ | |
− | + | & = & \displaystyle{-\frac{3}{2}.} | |
+ | \end{array}</math> | ||
|} | |} | ||
+ | |||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
!Final Answer: | !Final Answer: | ||
|- | |- | ||
− | |'''(a)'''& | + | | '''(a)''' <math style="vertical-align: 0px">9</math> |
|- | |- | ||
− | |'''(b)'''& | + | | '''(b)''' <math style="vertical-align: 0px">\infty</math> |
|- | |- | ||
− | |'''(c)'''& | + | | '''(c)''' <math style="vertical-align: -15px">-\frac{3}{2}</math> |
|} | |} | ||
[[009A_Sample_Final_1|'''<u>Return to Sample Exam</u>''']] | [[009A_Sample_Final_1|'''<u>Return to Sample Exam</u>''']] |
Latest revision as of 17:10, 20 May 2017
In each part, compute the limit. If the limit is infinite, be sure to specify positive or negative infinity.
(a)
(b)
(c)
Foundations: |
---|
L'Hôpital's Rule, Part 1 |
Let and where and are differentiable functions |
on an open interval containing and on except possibly at |
Then, |
Solution:
(a)
Step 1: |
---|
We begin by factoring the numerator. We have |
|
So, we can cancel in the numerator and denominator. Thus, we have |
|
Step 2: |
---|
Now, we can just plug in to get |
|
(b)
Step 1: |
---|
We proceed using L'Hôpital's Rule. So, we have |
|
Step 2: |
---|
This limit is |
(c)
Step 1: |
---|
We have |
|
Since we are looking at the limit as goes to negative infinity, we have |
So, we have |
|
Step 2: |
---|
We simplify to get |
|
Final Answer: |
---|
(a) |
(b) |
(c) |